Exploring Research Development on Renewable Energy Technology Innovation in Sustainable Development - Judijanto, Loso; Yusuf, Ramdan; Al Imran, Hamzah; Wahyudi, Eko (Westscience Press, 2023)
This research conducts a comprehensive bibliometric analysis to explore the development of renewable energy technology innovation research in the context of sustainable development. Through an examination of scholarly publications, citation patterns, and keyword occurrences, this study aims to provide a nuanced understanding of the current state of research in this critical field. Seminal works, influential authors, thematic clusters, and keyword frequencies are examined to uncover the multidimensional aspects of renewable energy technology innovation and its intersection with sustainable development. The synthesis of these insights informs researchers, policymakers, and industry stakeholders, guiding them toward a holistic approach in addressing the challenges and opportunities at the nexus of renewable energy, technology innovation, and sustainability.